Geospatial distribution of heavy metals in rice soils of northwestern Peru - Tarrillo Julca, Ever; Arce Inga, Marielita; Torres Herrera, Pedro Antonio; Tineo Flores, Daniel; Taboada Mitma, Victor Hugo; Cruz Luis, Juancarlos Alejandro; Rojas Briceño, Nilton B.; Atalaya Marin, Nilton; Gómez Fernández, Darwin; Goñas Goñas, Malluri (Nature Portfolio (Springer Nature), 2025)
The presence of heavy metals in agricultural soils poses a threat to the development of sustainable agriculture and ensuring food security. The objective of this study was to evaluate the geospatial distribution of heavy metals in rice-growing soils within the Amojú River Basin, Jaen, Peru. Ninety-five soil samples were collected randomly, covering four altitudinal ranges, namely, very low (374–450 m above sea level (m a.s.l.)), low (450–571 m a.s.l.), medium (571–701 m a.s.l.) and high altitudes (701–1,034 m a.s.l.), and different agronomic management stages, including four phenological phases (seedling, tillering, filling and ripening) and two agricultural practices (resting and stubble burning). The evaluation was conducted via physicochemical analysis, the single-factor pollution index, and spatial interpolation techniques through the empirical Bayesian kriging (EBK) method. The results indicated that the contents of cadmium (Cd) and chromium (Cr) exceed the limits established in the Environmental Quality Standards (EQSs) for agricultural soils, with maximum Cd and Cr concentrations of 2 and 21 mg kg ⁻¹, respectively, mainly in very low-altitude areas (374–450 m a.s.l.). The single-factor pollution index results indicated slight Cd contamination and intense Cr contamination. Likewise, high levels of arsenic (As), Cd, and Cr were detected in soils managed via stubble burning, reaching 2, 2, and 16 mg kg ⁻¹, respectively. The highest Cr concentrations were located in the northeastern and western parts of the study area, whereas the highest Cd concentrations occurred in the northeastern and southwestern parts. These concentrations may be associated with potential contamination sources, with the use of phosphate fertilizers, water for cultivation, and soil erosion as key contributors. This study highlights the potential risk to rice productivity and crop safety, emphasizing the importance of implementing sustainable agricultural practices and monitoring strategies for heavy metals in soils associated with crops.